2004
DOI: 10.1080/07315724.2004.10719425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium on Essential Oil Formation of Genetically Transformed and Non-Transformed Chamomile Cultures

Abstract: We identified alpha-selinene, as a new component in these hairy roots. We studied the growth rate of A4-Y clone on the cited media, containing MgSO4 concentrations: 0; 185; 370 and 740 mg/l. The cultures grew most in medium containing 740 mg/l of MgSO4. Essential oil content was compared from hairy root cultures of different Mg containing media and measured by GC and GC-MS methods. Mg has a similar effect on hairy roots as on organized cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Hank et al (2003) report that increased MgSO 4 application to genetically modified root cultures of the herbaceous plant species belladonna (Atropa belladonna L.), which is produced for the production of tropane alkaloids for medicinal applications, positively affected growth and tropane alkaloid production. Szöke et al (2004) found that MgSO 4 supply to chamomile (Matricaria recutita L., formerly Chamomilla recutita L.) root culture (widely known in classical and folk medicine for its contents in essential oils) positively affected not only growth of the root cultures (genetically modified hairy root and wild-type cultures) but also improved the quality and quantity of essential oil production. Both studies intended to improve methodologies in biotechnology.…”
Section: Magnesium In Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hank et al (2003) report that increased MgSO 4 application to genetically modified root cultures of the herbaceous plant species belladonna (Atropa belladonna L.), which is produced for the production of tropane alkaloids for medicinal applications, positively affected growth and tropane alkaloid production. Szöke et al (2004) found that MgSO 4 supply to chamomile (Matricaria recutita L., formerly Chamomilla recutita L.) root culture (widely known in classical and folk medicine for its contents in essential oils) positively affected not only growth of the root cultures (genetically modified hairy root and wild-type cultures) but also improved the quality and quantity of essential oil production. Both studies intended to improve methodologies in biotechnology.…”
Section: Magnesium In Biotechnologymentioning
confidence: 99%
“…In another 2-year study Ram and Bose (2000) found that despite the high nutrient demand of mandarin orange effects of foliar Mg and micronutrient (Cu, Zn, Fe, B) application on TSS, total sugar, reducing sugars and fruit acidity were not significant, even though the fruit yield was indeed higher (except when copper was applied together with the other nutrients). in-vitro + (production of tropane alkaloid production), + (quantity and quality of essential oil production by hairy root culture systems) Hank et al (2003), Szöke et al (2004) n.d. not detected, + positive effect, − negative effect, 0 no effect observed (the terms 'positive' and 'negative' refer to increasing and decreasing effects, respectively, irrespective of whether these trends are improving or reducing the quality) a Conclusion on Mg effects can be drawn as dolomite and calcite were comprehensively compared in this study b At harvest and after cold storage, respectively…”
Section: Tropical Fruits/exotic Fruitsmentioning
confidence: 99%
“…Alternatively, the product can be bound non-covalently to Anethum graveolens (dill) Essential oil yield was only 0.02%, compared to 0.06%, 0.3% and 2% of normal plant root, leaf and fruits, respectively [68] Artemisia absinthium Essential oil containing 47% neryl isovalerate (precursor of a-fenchene) and 6% neryl butyrate [69] Chamomila recutita (chamomile) Low amounts of essential oil, containing mainly farnesene. Had also selinene as a new compound [70] Coluria geoides Eugenol yield was 10-fold lower than in normal roots [71] Cucumis melo 2-Hexenal as main ingredient [72] Leontopodium alpinum 2,3-Dihydro-2,6-dimethyl-4H-benzopyran-4-one in the essential oil of hairy and normal roots. Similar constituency of the oils [73] Levisticum officinale (lovage) Essential oil yield was 3-10% of that of normal roots.…”
Section: Biotransformations Biotransformations By Plant and Microorgamentioning
confidence: 99%
“…This plant has 1% extract. The blue color of the extract results from a lipophenolic compound called camazolin (4). Chamomile contains compounds such as coumarin phytoestrol, flavonoids, and acrolin (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%